(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Under Article 19(1)(a) of the Indian Constitution, which guarantees freedom of speech andexpression, the media is granted freedom of the press. As a result of this freedom, the media is allowed tocontinue reporting the news and publishing articles based on interviews with witnesses and otherparties about cases that are currently under investigation by a court of law. However, by doing so, themedia risks prejudicing the case and interfering with the administration of justice, both of which willnegatively impact the outcome of the investigation, The media’s role in high-profile cases can lead toprejudice or bias views that have a significant impact on the administration of justice. In some cases,judges must be impartial in rendering judgment based solely on the facts and evidence presented incourt of law, which may further compel the judge to find the accused guilty. This essay focuses on thetension that arises between press freedom, a fair trial, and judicial independence as a result of a trial thatwas covered by the media.